PENGARUH TEKNIK KUNJUNGAN LAPANGAN TERHADAP KEMAMPUAN MENULIS PARAGRAF DESKRIPSI SISWA KELAS X SMA SWASTA PRAYATNA MEDAN TAHUN AJARAN 2012/2013 - DEWI SAFITRI RITONGA (Universitas Negeri Medan, 2014)
This study aimed to describe the technique of site visits terhadap pengaruh writingabilities paragraf description of class X High School Private Lessons PrayatnaMedaan Year 2012/2013. This study population is all private school studentskelaas X Prayatna as many as 320 people. Samples were taken at random by 600rang, 30 0rang for experimental class and 30 for grade control.The instrument used was a test to write a paragraph description. The averagevalue of the experimental class was 75.6, while for the control class is 68.6Thus, it can be said that the average value of the ability to write a paragraphdescription of the experimental class higher than the control Kellas.Hypothesis testing is performed using test test